Analisis Hubungan Karakteristik Sosial Ekonomi Petani dengan Penerapan Teknologi Sistem Tanam Jajar Legowo pada Padi Sawah di Kabupaten Batanghari - Uliya (Fakultas Pertanian, Universitas Warmadewa, 2020)
Uliya, Analysis of the relationship of socio-economic characteristics of farmers with the application of legowo row planting system technology on rice paddy in Batanghari District. This study aims to analyze the socio-economic characteristics of farmers planting system of row legowo on wetland rice in Batanghari Regency, analyzing the application of legowo row planting system technology on rice paddy in Batanghari District. To analyze the correlation between socio-economic characteristics of farmers with the application of legowo row planting system technology on paddy rice in Batanghari District. This research was conducted in Batanghari District in Maro Sebo Ulu District and Mersam Sub-district. Consisting of 10 Villages and District Mersam consists of 12 Villages. Total respondents are 70 farmers. To analyze the data used descriptive analysis, to determine the relationship of socio-economic characteristics of farmers with the application of technology planting system row legowo rice field in Batanghari district used non parametric test through correlation coefficient test Rank Spearman. Characteristics of socio-economic of row legowo farmers in Batanghari Regency mayoritas aged 45-49 years, farming experience <9 years, dominant education at elementary education level, land area of wetland rice farming area of 1.1-100 ha, range of 4-6 people as many as 45 people. Implementation of legowo row planting system technology on paddy field covers land preparation, making of planting line, planting, fertilizing, weeding, pest and disease control. Relationship of socio-economic characteristics of farmers with the application of technology obtained age with the application of technology, seen from ρ arithmetic 0.55353> ρ table 0.235, farming experience with the application of legowo java planting system system where ρ hit 0.65622> ρ table 0.235, education shows relationship which is negative with the application of technology where ρ arithmetic 0.124259 <ρ table 0.235, farm land area shows a positive relationship with the application of technology where ρ count 0.68428> ρ table 0.235, the number of family members shows a positive relationship with the application of technology where ρ count 0,55276> ρ table 0,235.